2021
DOI: 10.3389/fphy.2020.586087
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Metasurface: From Principle to Smart Metadevices

Abstract: Metamaterials are composed of periodic subwavelength metallic/dielectric structures that resonantly couple to the electric and magnetic fields of the incident electromagnetic waves, exhibiting unprecedented properties which are most typical within the context of the electromagnetic domain. However, the practical application of metamaterials is found challenging due to the high losses, strong dispersion associated with the resonant responses, and the difficulty in the fabrication of nanoscale 3D structures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(91 citation statements)
references
References 198 publications
(263 reference statements)
0
91
0
Order By: Relevance
“…The plasmonic nanorods experience a rapid phase shift with different amplitudes by varying their length and opening angle, as demonstrated in Figure 1 C. The physics of the V-shaped-based antenna and its systematic model were explored in great depth by Capasso’s group. The crossed polarized scattered light can possess a wide range of phases and amplitudes achieved by altering the antenna geometry, orientation, and antenna polarization as first proven by Yu et al and subsequently demonstrated by Ni et al in mid-infrared and near-infrared, respectively [ 25 , 26 ]. The antennas in the array are shaped and oriented so that they exhibit a variety of resonant properties.…”
Section: Principle Of Arbitrary Wavefront Modulation For Metasurfacementioning
confidence: 99%
“…The plasmonic nanorods experience a rapid phase shift with different amplitudes by varying their length and opening angle, as demonstrated in Figure 1 C. The physics of the V-shaped-based antenna and its systematic model were explored in great depth by Capasso’s group. The crossed polarized scattered light can possess a wide range of phases and amplitudes achieved by altering the antenna geometry, orientation, and antenna polarization as first proven by Yu et al and subsequently demonstrated by Ni et al in mid-infrared and near-infrared, respectively [ 25 , 26 ]. The antennas in the array are shaped and oriented so that they exhibit a variety of resonant properties.…”
Section: Principle Of Arbitrary Wavefront Modulation For Metasurfacementioning
confidence: 99%
“…Interestingly, an assembly of nanoparticles can bring about even more subtle control over linear and nonlinear scattering [17,18]. Specifically, for artificial 3D structures made of a periodic or pseudo-periodic arrangement, a strong magnetic response can be obtained, opening up the possibility to achieve negative refractive index within a certain wavelength range [19]. This ultimately led to the emergence of nonlinear metamaterials [16,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In order to simplify the optical system before the sensor and to maintain a high image quality, optical designers have to find new degrees of freedom in their designs. Several avenues have been thus explored, such as freeform optics [1], GRIN (gradient index) optics [2] and metasurfaces [3]. GRIN optics involve creating a spatial variation of the refractive index in the material.…”
Section: Introductionmentioning
confidence: 99%